The Relationships between Patient Satisfaction and Loyalty in The Private Hospital Industry - S Mortazavi; M Kazemi; A Shirazi; A Aziz-Abadi (Tehran University of Medical Sciences, 2009)
Background: In today's competitive world, organizations' survival and success depends on satisfying customer needs and expectations. This is particularly important in health care sector where quality of service and customer relations are the key success factors. The purpose of this research was to determine whether there was a relationship between patient satisfaction and loyalty to the service provider. Methods: A total of 240 patients in four private hospitals were invited to complete a survey questionnaire. Both parametric and nonparametric research analysis were performed to test the research hypotheses. In addition, sensitivity analysis was applied to identify the most critical satisfaction dimensions that provide the highest return for management effort and financial investment. The study used six specific-satisfaction dimensions, including nursing care, operating room, admission and administrative service, meal, cost and patient room to propose its hypotheses. Results: The patient overall satisfaction was mostly affected by the nursing care, meal, patient room as well as admission and administrative services, respectively. Further, we found that patient overall satisfaction and loyalty were positively correlated so that one unit increase in patient overall satisfaction increases patient loyalty by 54% to 77%. Conclusion: Hospitals in devising their long-term strategy should pay sufficient attention to the development of their human resources. Such a strategy should be leveraged on attracting and retaining competent and customer-oriented nursing and administrative staff, investing in continuous professional development of staff and using advanced technologies to improve the quality and speed of customer services.